Can Suspicious Ultrasound Features Predict BRAFV600E Status in Papillary Thyroid Cancer? - Khadra, Helmi (Eur Thyroid J, 2018)
BACKGROUND: Papillary thyroid carcinoma (PTC) can be predicted from certain suspicious ultrasound (US) features of thyroid nodules. The aim of this study was to examine if these suspicious features can predict the more aggressive PTC associated with B-type Raf kinase (BRAFV600E) mutation. METHODS: This was a retrospective review of prospectively collected data on patients with PTC and known BRAFV600E status. All patients underwent preoperative US by the same surgeon who performed all the operations. We divided patients into BRAFV600E positive and negative groups. All ultrasonographic data were collected including nodule size, echogenicity, solid or cystic nature, presence of calcifications, irregular margins, and internal vascularity. RESULTS: Of 141 patients with PTC, BRAFV600E mutation was detected in 48 (34.0$) patients. There was no significant difference in nodule size (2.06 cm ± 1.37 vs. 2.15 cm ±1.55, p = 0.75) between BRAFV600E positive and negative groups. BRAFV600E positivity was associated with higher rates of hypoechogenicity (57.5$ vs. 36.6, p = 0.02), calcifications (48.9 vs. 19.4$, p < 0.01), and irregular margins (21.3 vs. 6.5$, p < 0.01). There was no significant difference in the noncystic nature or internal vascularity between BRAFV600E positive and negative groups. The presence of all suspicious US features is associated with a positive predictive value of 100.0$. In the absence of all suspicious features, the negative predictive value was 84.2$. When suspicious lymph nodes (LNs) detected by preoperative US were compared, there was no significant difference between BRAFV600E positive and negative groups (30.6 vs. 21.7$, p = 0.35). CONCLUSION: The presence of multiple suspicious US findings of thyroid nodules can predict the BRAFV600E mutation status of papillary thyroid cancer nodules. The highest accuracy overall (93.2$) was achieved by combining calcification, irregular margins, and hypoechogenicity with extrathyroidal extension and LN metastasis. Future multi-institutional studies are warranted to help surgeons with risk stratification and operative planning for patients with papillary thyroid cancer.